Neutron and neutron-induced gamma ray signatures as a template matching technique for explosives detection - Brewer, Rebecca L. (Kansas State University, 2009)
Improvised explosives devices (IEDs) are the cause of many casualties worldwide. Current methods for detecting IEDs are insufficient. A signature-based scanning technique based upon the fact that explosives consist primarily of hydrogen, oxygen, nitrogen, and carbon is examined as a possible rapid, standoff method for detecting IEDs. Devices employing this method rely on a template-matching technique in which the detector responses acquired through neutron and photon interrogation are compared to responses from a known explosive. A figure-of-merit is calculated to determine how well the template and the unknown match. This thesis explores the feasibility of employing the neutron interrogation aspect of this method.
Keywords: Neutron; Explosive; Detection; Engineering, Nuclear (0552)